About Nostalgia and Architecture: Identifying Nostalgic Architecture Properties Employing Grounded Theory Method - Rashid Jafari; Niloufar Malek; Hamid Nadimi (صفه)
Experience of being in places that associate meanings or memories related to past can lead to a sweet feeling. Sometimes with this experience, a sweat-bitter emotional feeling encompasses one. This feeling which appears as the result of lack of a desired situation and is usually associated with words expressing regret is called nostalgia. The architecture which can evoke nostalgia in people is called nostalgic architecture. Places with this affordance can lead to human’s sense of belonging to environment and present some properties of cognitive beauty that has been neglected so far. Sense of continuity of past, sense of familiarity because of associating familiar elements and meanings are the results of forming nostalgia in architecture. In the meantime due to changes caused by modernism, the nostalgic aspect of architecture has been less noticed as if it has been neglected. This research using classic grounded theory method tries to discover those properties of a place that their existence can lead to a nostalgic architecture. Therefore we hope that it works as a stepping stone to provide tools for architects in order to create nostalgic architecture by using them and improve the quality of living environment.